Single-Well Dynamic Permeability Splitting Algorithm and Classification Evaluation: A Case Study of a Super-Thick Carbonate Reservoir in the Middle East - Cao, Peng; Wang, Yongjun; Qiao, Zhanfeng; Zhu, Guangya; Su, Haiyang; Shao, Guanming; Gong, Jie; Deng, Haiyang (Frontiers in Energy Research, 2022)
The permeability interpretation accuracy of single wells in the Middle East super-thick carbonate reservoir can hardly meet the actual demand of water injection development. Therefore, this study develops an iterative split algorithm to calculate single-well segmental dynamic permeability and SPI (specific production index) based on the dynamic and static well test, PLT (production log test), production test, and logging interpretation data. Moreover, the dynamic permeability classification evaluation index was optimized. The detailed steps are as follows: 1) The liquid supply of a single well is split according to tp PLT. 2) For some production intervals, the log interpretation data are applied to carry out the second iteration splitting of formation coefficient and fluid supply. 3) The proportion of liquid supply in the stratification section is calculated based on the calculation results of steps 1 and step 2. 4) The total formation coefficient of well test interpretation is divided based on the calculation results of step 3. 5) The dynamic permeability and SPI are calculated. The research results show that the dynamic permeability and SPI of a single well are accurate to the scale of one meter from the several original meters to tens of meters, which can better meet the needs of water injection development. In addition, SPI can be used as an essential index for permeability classification evaluation. Taking the Halfaya Oilfield and the Mishrif format reservoir as examples, the low penetration rate of the MB1-2 high penetration rate is 200md and the lower specific production index limit is 0.35 bbl/(d·m·psi), respectively. The dynamic foundation of the high-permeability layer is identified. This method offers a new idea for the title of high-permeability streaks. Moreover, this method can provide the scientific basis for correcting the permeability attribute model, water injection plan optimization, single-well completion cementing scheme, and water coning control, which can be popularized and applied in the same reservoirs.